Effect of Time-Restricted Feeding on Body Weight and Cardiometabolic Risks: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ruanpeng, Darin (J Endocr Soc, 2021)
Introduction: Time-restricted eating (TRE) or time-restricted feeding (TRF), a form of intermittent fasting (IF) when food consumption is restricted to a 4–12 hour window, poses unique possible health benefits that allow the nutrient to work in harmony with circadian rhythm. Whether TRF is effective in weight loss and cardiometabolic profile compare to usual diet is controversial. We conducted a meta-analysis of randomized control trials to investigate the weight and metabolic effects of TRF in humans. Methods: The systematic review was conducted according to the PRISMA guidelines. The literature search was conducted in MEDLINE, EMBASE, and CENTRAL from database inception to November 30, 2020. The search terms included time restricting feeding, time-restricted eating, periodic fasting, intermittent fasting, and periodic fasting. The eligibility criteria included a randomized controlled trial (RCT) comparing the effect of TRF as an intervention and control diet on weight and cardiometabolic risks in individuals with overweight (BMI 23–26.9 kg/m(2) in Asian and 25–29.9 kg/m(2) in others) or obesity (BMI≥27 kg/m(2) in Asian and ≥30 kg/m(2) in others) with study duration of at least 8 weeks. The primary outcome is the change in body weight between preintervention and postintervention. The secondary outcome is the change in total fat mass and lean mass, HDL, LDL, and triglycerides. Pool mean differences (MD) with 95% confidence interval (CI) were calculated for each outcome. Results: Four articles met the inclusion criteria and were included in this systematic review and meta-analysis. There were 511 participants with BMI 24 kg/m(2) and above and aged between 18 and 65. TRF was defined as a 4–8 hours ad-lib unrestricted eating in 24 hours. The control diet was defined as ad-lib eating per usual habits. There was a significant improvement in weight and body composition in the TRF group. The mean weight loss was -2.08 kg (95% CI: -3.49 to -0.68) greater among TRF group. There was a significant total fat mass and lean mass loss in the TRF group with the MD of -1.29 kg (95% CI: -2.04 to -0.54) and -0.59 kg (95% CI: -1.15 to -0.03), respectively. There was no significant change in HDL, LDL, or triglycerides comparing between TRF and control diet. Conclusion: This systematic review and meta-analysis of RCT showed that TRF with no calories restriction resulted in significant decreased in weight, fat mass, and a slight decreased in total lean mass compared with control diet. Our findings support TRF as an effective lifestyle intervention for weight loss.